Strategi Diferensiasi dan Harga Sebagai Alat Untuk Meningkatkan Loyalitas Konsumen Klinik Auraku Bandung - Nicky Novianty; Yunika Komalasari; Wulan Yuliyana (Universitas Bunda Mulia, 2021)
Consumer Loyalty is a strongly held commitment to buy or re-subscribe to certain products or services in the future despite the influence of the situation and marketing efforts that have the potential to cause behavior change. This study aims to examine the influence of differentiation and price strategies in increasing consumer loyalty at Auraku Bandung clinic. The data analysis technique used descriptive verification method. The results showed that the differentiation strategy has a positive and significant effect in increasing consumer loyalty, price has a positive and insignificant effect in increasing consumer loyalty. Simultaneously the differentiation strategy and price together have a significant effect on consumer loyalty at Auraku Bandung clinic. Based on this research, Auraku Bandung clinic should continue to maintain and improve its differentiation strategy. The dimensions that must be improved in a differentiation strategy are product, service, and image. By having superior products, excellent services and a good corporate image, the company will be able to provide prices according to the quality they provide. This is done in order to continue to provide satisfaction to consumers and so that consumers return in the future.